Study on the Transmission Characteristics of Polarized Laser in the Complicated Dust Environment on Mars. (4th February 2022) - Yang, Yu-Feng; Ke, Jian; Han, An-Li; Xu, Rui-Na
Abstract : In this paper, for the dust environment in complicated atmospheric on Mars, the Martian atmosphere is vertically stratified based on the vertical distribution characteristic of Martian dust particles. Combining the number concentration and particle size distribution of each layer of dust, the transmission characteristics of polarized laser in the Martian dust are studied by using the polarized Monte Carlo method. The results show that among the six selected wavelengths, the transmittance of the wavelength of 7.46 μ m in Martian dust is the largest, while the laser intensity attenuation of the wavelength of 0.49 μ m in Martian dust is the largest. The horizontally polarized laser of the wavelength of 0.55 μ m (effective variance b = 0.1 μ m) is taken as an example; the depolarization degree of the polarized laser under stratified conditions increases from the minimum value of 3.5440157 e − 4 at 0 km to the maximum value of 0.0092563 at 24 km, with an increase of 0.00890189843; while the depolarization degree under nonstratified conditions increases from the minimum value of 1.2678582 e − 4 at 0 km to the maximum value of 0.0045636 at 24 km, with an increase of only 0.004436842, the degree of depolarization under the condition of stratified is greater than that of nonstratified. On the whole, for different effective variance b, the variation trend of the polarization parameter with height for different polarized laser is basically identical.